2016
DOI: 10.1007/s11356-016-7239-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use conversion and fertilization on CH4 and N2O fluxes from typical hilly red soil

Abstract: Land use conversion and fertilization have been widely reported to be important managements affecting the exchanges of greenhouse gases between soil and atmosphere. For comprehensive assessment of methane (CH 4 ) and nitrous oxide (N 2 O) fluxes from hilly red soil induced by land use conversion and fertilization, a 14-month continuous field measurement was conducted on the newly converted citrus orchard plots with fertilization (OF) and without fertilization (ONF) and the conventional paddy plots with fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
5
15
0
Order By: Relevance
“…The mean annual CH 4 and N 2 O fluxes from rice paddies in this study were 303.9 kg C ha −1 and 3.8 kg N ha −1 , respectively, over the three cultivation years. These values were within the ranges identified by previous studies in double rice-cropping system with similar fertilization rates 6 , 9 , 28 , 37 , but were much higher than those from other studies in single rice-cropping systems 3 , 15 , 38 . The mean annual CH 4 and N 2 O fluxes from the paddy field-converted citrus orchard were −1.19 kg C ha −1 and 10.88 kg N ha −1 , respectively, over the entire study period, which were generally close to previous observations 18 , 39 , 40 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The mean annual CH 4 and N 2 O fluxes from rice paddies in this study were 303.9 kg C ha −1 and 3.8 kg N ha −1 , respectively, over the three cultivation years. These values were within the ranges identified by previous studies in double rice-cropping system with similar fertilization rates 6 , 9 , 28 , 37 , but were much higher than those from other studies in single rice-cropping systems 3 , 15 , 38 . The mean annual CH 4 and N 2 O fluxes from the paddy field-converted citrus orchard were −1.19 kg C ha −1 and 10.88 kg N ha −1 , respectively, over the entire study period, which were generally close to previous observations 18 , 39 , 40 .…”
Section: Discussionsupporting
confidence: 82%
“…The periodic waterlogging-drainage alteration episodes and intensive inputs of organic material and nitrogen fertilizer in paddy fields may provide a suitable soil environment and accessible substrate for CH 4 and N 2 O emissions 3 , 4 . Many studies have demonstrated high CH 4 but relatively low N 2 O emissions from rice paddies because anaerobic conditions limit nitrate availability and because strict anaerobiosis favours complete denitrification to nitrogen gas (N 2 ) 5 , 6 . However, N 2 O emissions are generally high in upland soils, especially after fertilization or irrigation events, due to the tight coupling between nitrification and denitrification 7 9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations